Evaluasi Tata Kelola Sistem Keamanan Teknologi Informasi Menggunakan Framework COBIT 5 Fokus Proses APO13 dan DSS05 (Studi Pada PT Martina Berto Tbk) - Raja Gantino Mufti; Suprapto Suprapto; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
PT Martina Berto Tbk is a manufacturing, marketing, research and development company within the Martha Tilaar Group. Currently, the company has implemented systems and information technology in support of corporate operations carried out by the Corporate IT department. However, there are some deficiencies in the application, especially in terms of security, such as security incidents that often arise and attacks to the corporate servers. To prevent these things from happening again, it is necessary to know how far the governance of the company's information technology security system by conducting an evaluation, because with the evaluation, recommendations in the form of what actions should be done can be generated, so that security incidents won't happen again. The research was conducted to determine the Capability Level on governance of information technology security systems in PT Martina Berto Tbk using COBIT 5 framework process domain APO13 and DSS05. The research data were obtained from interviews, questionnaires and observations. The results show the Capability Level on the process domain APO13 and DSS05 are at level 1, while the desired Capability Level in both process domains is level 2, leaving a gap of 1. After knowing the current and desired Capability Level, then made a recommendation based on SWOT analysis. Recommendations are given such as the establishment of a special unit of information security, making documents related to the management and enhancement of information security and information security risk plotting, making operational standard documentation of security services as well as updating technical information technology and monitoring on a regular basis.